2010
DOI: 10.4141/cjps10037
|View full text |Cite
|
Sign up to set email alerts
|

Influence of N fertilization method on weed growth, grain yield and grain protein concentration in no-till winter wheat

Abstract: . 2010. Influence of N fertilization method on weed growth, grain yield and grain protein concentration in no-till winter wheat. Can. J. Plant Sci. 90: 637Á644. Applying polymer-coated urea (PCU) instead of uncoated urea may benefit winter wheat (Triticum aestivum L.) production by reducing weed growth or increasing grain yield and protein concentration. Field trials were conducted for 3 yr under rainfed and irrigated conditions in Lethbridge and 2 yr under rainfed conditions in Lacombe to determine potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Conversely, kernel and test weight were greater for ESN® vs. one or more of the other forms. In other studies, grain yield and protein concentration in winter wheat were either similar or incrementally favourable for ESN® over uncoated urea in regions of the northern Great Plains (Beres et al 2010b;McKenzie et al 2010). …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, kernel and test weight were greater for ESN® vs. one or more of the other forms. In other studies, grain yield and protein concentration in winter wheat were either similar or incrementally favourable for ESN® over uncoated urea in regions of the northern Great Plains (Beres et al 2010b;McKenzie et al 2010). …”
mentioning
confidence: 99%
“…The results suggest split applications of N might be most efficient for yield and protein optimization when combined with an enhanced efficiency urea product, particularly with urease or urease+nitrification inhibitors, and if the majority of N is applied in spring. Lacombe and Lethbridge, Alberta (Beres et al 2010a;Beres et al 2010c), and anecdotal reports from industry, indicate that this standard can be difficult to meet; therefore, most grain buyers will accept 110 g kg -1 and blend to specifications accordingly in an effort to provide a consistent supply of winter wheat with this quality profile. Feed markets and the emergence of the ethanol feedstock market may negatively impact supplies of CWRW if producers perceive less risk and increased profitability in targeting starch production over protein production.…”
mentioning
confidence: 99%
“…In contrast, several studies have found that CRU provides a significant yield benefit as compared with urea and other fertilizer types (Beres et al 2010;Ziadi et al 2011;Yang et al 2011). A 3-yr potato production study in eastern Quebec (Ziadi et al 2011) found CRU to be a promising N source to increase potato yield and NUE.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Marketable yield was higher with CRU than other treatments, but the authors noted N release in CRU was dependent on temperature and moisture, so the results could differ depending on location and weather. In studies by Yang et al (2011) in northern China and by Beres et al (2010) in Canada that examined CRU effects on wheat yield and quality, the NUE and yield of wheat was improved with the use of CRU compared with urea, but wheat protein content did not differ with CRU compared with other sources.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation